1994
DOI: 10.1103/physrevd.50.r1
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the Gottfried sum

Abstract: Rapid Communications are intended for important new results which deserve accelerated publication, and are therefore given priority in editorial processing and production AR. apid Communication in Physical Review D should be no longer than five printed pages and must be accompanied by an abstract. Page proofs are sent to authors, but because of the accelerated schedule, publication is generally not delayed for receipt of corrections unless requested by the author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
165
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 329 publications
(186 citation statements)
references
References 9 publications
20
165
1
Order By: Relevance
“…[43]. However, the lower x NMC data [38,39] showed that this idea was untenable. Other attempts to understand the sum rule violation centered around the extraction of the neutron distribution from deuterium or other light nuclear data.…”
Section: Current Experimental Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…[43]. However, the lower x NMC data [38,39] showed that this idea was untenable. Other attempts to understand the sum rule violation centered around the extraction of the neutron distribution from deuterium or other light nuclear data.…”
Section: Current Experimental Studiesmentioning
confidence: 99%
“…Experiments have clearly shown that not only is u = d but also that the difference is a strong function of x [39,41]. A number of models have been proposed to describe this difference, including meson clouds, Pauli blocking, chiral models, and charge symmetry violation.…”
Section: Light Sea Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…the non-singlet structure function F p 2 − F n 2 and the Gottfried sum S G = (F p 2 − F n 2 )dx/x can be determined. For the latter, it was shown that the simple quark-model expectation of 1/3 is not reached [42,43] and hence the light quark sea is not flavor-symmetric. We do not elaborate on these aspects here, as our data add only limited additional information in the DIS region.…”
Section: Jhep05(2011)126mentioning
confidence: 99%